2008
DOI: 10.7202/017932ar
|View full text |Cite
|
Sign up to set email alerts
|

Évaluation de la vulnérabilité à la pollution potentielle de la nappe côtière alluvionnaire de Meltine-Ras Jebel-Raf Raf (Nord-Est tunisien) selon les méthodes paramétriques DRASTIC, SINTACS et SI

Abstract: La nappe alluvionnaire de Metline-Ras Jebel-Raf Raf (gouvernorat de Bizerte, côte Nord Est de la Tunisie), qui occupe une superficie de 35 km2, représente une ressource économique jugée prioritaire du fait qu’elle est utilisée dans les domaines d’irrigation et de consommation domestique. L’aire de la nappe est occupée essentiellement par des zones agricoles caractérisées par une utilisation de plus en plus importante des engrais chimiques qui représentent, en plus des rejets des zones industrielles, un ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…As a result, the DRASTIC model and similar methods are very e cient but only consider a limited set of criteria intrinsic to the aquifer (Babiker et al, 2005;Rahman 2008; Hamza et al, 2008;Saidi et al, 2009;Yin et al, 2011;Muhammad et al, 2015;Ghosh et al, 2015;Shrestha et al, 2017;Victorine Neh et al, 2015;Oke 2020). In the case of shallow aquifers located in areas characterized by on-site sanitation, the sources of faecal pollutants (septic tanks or latrines) are not intrinsic to the shallow aquifer and encroach on a good part of the thickness of the unsaturated zone.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the DRASTIC model and similar methods are very e cient but only consider a limited set of criteria intrinsic to the aquifer (Babiker et al, 2005;Rahman 2008; Hamza et al, 2008;Saidi et al, 2009;Yin et al, 2011;Muhammad et al, 2015;Ghosh et al, 2015;Shrestha et al, 2017;Victorine Neh et al, 2015;Oke 2020). In the case of shallow aquifers located in areas characterized by on-site sanitation, the sources of faecal pollutants (septic tanks or latrines) are not intrinsic to the shallow aquifer and encroach on a good part of the thickness of the unsaturated zone.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different overlay and index methods, DRASTIC is one of the most popular due to its performance and ease of use (Barbulescu 2020). In the last two decades, DRAS-TIC has been employed in several studies to assess groundwater vulnerability in Asia (Rahman 2008;Babiker et al 2005;Yin et al 2011;Muhammad et al 2014;Ghosh et al 2015;Shrestha et al 2017), Africa (Ojuri and Bankole 2013;Jourda et al 2007;Saidi et al 2009;Hamza et al 2008Hamza et al , 2010Neh et al 2015;Oke 2020) and the Americas (Klug 2009;Agyemang and Beauty 2017). DRASTIC does not, however, explicitly consider spatial variability in anthropogenic factors that may be of critical importance in rapidly urbanizing, low-income areas (Singh et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Modifications to DRASTIC have been developed to explicitly represent groundwater vulnerability to anthropogenic pollution from surface/sub-surface sources. SINTACS (Civita et De Maio 1997), DRASTIC_N (Voutchkova et al 2020) and the Susceptibility Index or SI (Riberio et al 2000) are examples of these, which have demonstrated efficacy in assessing groundwater vulnerability in many environments (Batista 2004;Frances et al 2002;Stigter et al 2006;Hamza et al 2008;Ake et al 2011;Afonso et al 2016;Ribeiro et al 2017;Batchi et al 2017;Si et al 2017;Marjuanto et al 2019;Voutchkova et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Modifications to DRASTIC have been developed to explicitly represent groundwater vulnerability to anthropogenic pollution from surface/sub-surface sources. SINTACS (Civita et al, 1997), DRASTIC_N (Voutchkova et al, 2020) and the Susceptibility Index or SI (Riberio et al, 2000) are examples of these, which have demonstrated efficacy in assessing groundwater vulnerability in many environments (Batista S, 2004;Frances et al, 2002;Lobbo-Ferreira et Oliveira, 2005;Stigter et al, 2006 ;Hamza et al, 2008 ;Ake et al, 2010 ;Afonso et al, 2016 ;Ribeiro et al, 2016 ;Batchi et al, 2017 ;Si et al, 2017 ;Armanuos et al, 2019 ;Marjuanto et al, 2019 ;Voutchkova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Among the different overlay and index methods, DRASTIC is one of the most popular due to its performance and ease of use (Barbulescu, 2020). In the last two decades, DRASTIC has been employed in several studies to assess groundwater vulnerability in Asia (Babiker et al, 2005;Yin et al, 2011;Ghosh et al, 2015), Africa (Jourda et al, 2007;Saidi et al, 2009;Hamza et al, 2008Hamza et al, , 2010Neh et al, 2014;Oke, 2020), and the Americas (Klug, 2009;Ferral et al, 2014;Agyemang and Beauty, 2017). DRASTIC does not, however, explicitly consider spatial variability in anthropogenic factors that may be of critical importance in rapidly urbanizing, lowincome areas (Singh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%